Strength of wood dowel from Mersawa, Kedondong Bulan and Kedondong Sengeh in UiTM forest / Wan Muhamad Farhan Wan Yusoff, Aizuddin Arif Abdul Ghani and Muhamad Faiz Mahmood - Wan Yusoff, Wan Muhamad Farhan; Abdul Ghani, Aizuddin Arif; Mahmood, Muhamad Faiz (2011)
This research is about the strength of wood dowel from Mersawa, Kedondong bulan and Kedondong sengeh. All the species are from DIP UiTM Forest. In this research we were comparing the strength of each species as dowel in making joints by using breaking load testing. Breaking load testing is a test to determine the load which causes fracture in a tensile, compression, flexure or torsion test. In tensile tests of textiles and yarns, breaking load also is called breaking strength. For this breaking load testing we were using model that used by Matthias Wandel, a famous writer and wood expert. Then, we used SPSS was to analyze all the data that we obtained from the breaking load testing.